New record of Liolaemus ditadai Cei, 1983 (Squamata, Liolaemidae) from Santiago del Estero province, Argentina - Avila, Luciano Javier (2015)
Liolaemus ditadai is a rare liolaemid lizardoriginally described from Salinas Grandes salt-pans flat,in the border between Cordoba and Catamarca Provincein central Argentina. Only a few specimens of this speciesare known. Here, we present a new record that result ina significant extension of the known distribution of thespecies, which is currently considered to be restricted toa small area in Salinas Grandes. In addition, we commenton previous records of the species in central Argentina.